2020
DOI: 10.1186/s13567-020-00771-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pathogenicity of subtype H9 avian influenza wild-type viruses from a wide geographic origin expressing mono-, di-, or tri-basic hemagglutinin cleavage sites

Abstract: An intravenous pathogenicity index (IVPI) of > 1.2 in chickens or, in case of subtypes H5 and H7, expression of a polybasic hemagglutinin cleavage site (HACS), signals high pathogenicity (HP). Viruses of the H9N2-G1 lineage, which spread across Asia and Africa, are classified to be of low pathogenicity although, in the field, they became associated with severe clinical signs and epizootics in chickens. Here we report on a pre-eminent trait of recent H9N2-G1 isolates from Bangladesh and India, which express a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…In this study, after virus adsorption, the cells were washed and then overlaid with 1% methylcellulose in medium without trypsin to prevent the release and spread of progeny virus, thereby enabling us to observe only foci that were a result of the initial input virus infection. Most H9N2 G1 lineage viruses, including CL80, CL42, and Em/R66, had HAs with mono- or dibasic cleavage sites, and their growth depended on trypsin ( 20 , 39 ). The viruses showed identical infectivity on MDCK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, after virus adsorption, the cells were washed and then overlaid with 1% methylcellulose in medium without trypsin to prevent the release and spread of progeny virus, thereby enabling us to observe only foci that were a result of the initial input virus infection. Most H9N2 G1 lineage viruses, including CL80, CL42, and Em/R66, had HAs with mono- or dibasic cleavage sites, and their growth depended on trypsin ( 20 , 39 ). The viruses showed identical infectivity on MDCK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that during serial passaging in chickens, the P2 position at HACS of the H9N2 virus was more polymorphic, and the amino acids N337K in the P2 position detected in the 6th passage 33 . The G1-lineage H9N2 viruses were adapted to birds and humans and induced more severe infections than the other representative lineage of H9N2 virus, and a basic amino acid in the P3 position of HACS formed an intermediate step towards a gain in pathogenicity 34 . In this study, we found that a sharp increase occurred after 2010 in the G1-lineage of H9N2 viruses with an identical HACS of the tribasic PAKSKR/G-motif from Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the histopathological and immunohistochemical examination and the basic semiquantitative scoring have been published in multiple independent manuscripts for most of the infection experiments previously (see [39][40][41][42][43][44][45][46]).…”
Section: Resultsmentioning
confidence: 99%